Pengaruh Reputasi Perusahaan dan Kualitas Layanan Elektronik terhadap Kepuasan Pengguna Aplikasi Layanan Jasa Keuangan Ajaib di Kota Surabaya - Supriatun; Ni Made Ida Pratiwi; Diana Juni Mulyati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
In conducting transactions in the capital market, assistance is needed from a third party or securities company as an intermediary that provides investment product buying and selling services. With the number of securities companies that exist today, creating increasingly fierce competition between each company. Improving service quality by presenting online investment applications is an option to reach more layers of society accompanied by dedication and commitment as a company that is responsible for the investment services provided. This study aims to analyze the effect of corporate reputation and e-service quality on user satisfaction of the Ajaib application in Kota Surabaya. Through quantitative research methods, 120 respondents were obtained whose sampling used non-probability sampling techniques by purposive sampling. The data that has been collected through an electronic questionnaire that has been tested for validity and reliability, is analyzed using the classical assumption test, hypothesis testing and multiple linear regression analysis using IBM SPSS statistic software ver. 25. The results showed that partially and simultaneously, there was an influence between corporate reputation and electronic service quality on user satisfaction of the Ajaib application in Kota Surabaya.